Combined topical therapy mixture can effectively and rapidly control atopic dermatitis lesions- a pilot study - Sabry, E.Y. (Journal of Pakistan Association of Dermatologists, 2016)
Background Topical steroids are the mainstay of therapy in atopic dermatitis. However, as massive colonization of lesional and non-lesional skin of atopic dermatitis patients with Staphylococcus aureus has been proved to exist and aggravate the skin lesions, thus topical antibiotics seem necessary to be added. New combined topical antibiotics and steroid formula eliminate forcefully the organism. Moreover, as topical medication penetrates a moist stratum corneum more effectively than it will penetrate a dehydrated stratum corneum, thus combining an emollient to atopic dermatitis therapy seems of utmost importance. Â Objective To evaluate the effectiveness of combining two topical steroids, an antibiotic and an emollient as a single mixture in effectively controlling atopic dermatitis lesions in a six weeks treatment period. Â Subjects and methods Thirty one females with atopic dermatitis were enrolled in this study. Disease severity was measured using the Severity Score of Atopic Dermatitis (SCORAD) index at baseline, 3 weeks and 6 weeks of therapy. They were treated with a mixture of mometasone furoate, fusidic acid and betamethasone valerate twice daily for six weeks. Â Results Out of the 31 enrolled cases, 20 (64.5%) satisfied the inclusion criteria. They all completed the 6-week treatment regimen and evidenced no side effects from therapy. Statistical comparison between baseline and after three and six weeks interval using ANOVA and Tukey’s multiple comparison tests revealed significant improvement of SCORAD index and its six clinical intensity signs with more effective improvement after the 6-week therapy. No correlation was ever detected by the Spearman test between index score and lesions’ site or with allergic co-morbidities. Â Conclusion The combined topical therapy mixture was effective and safe in rapidly controlling treated lesions. Â